Longitudinal Single Photon Emission Computed Tomography Neuroimaging as an Indication of Improvement in Psychiatric Disorders in a Community Psychiatric Practice - Thornton, John F.; Schneider, Howard; Cohen, Philip F.; DeBruin, Simon; Uszler, John Michael; Siow, Yin-Hui; McLean, Mary K.; van Lierop, Muriel J.; Pavel, Dan G.; Henderson, Theodore A. (Frontiers in Psychiatry, 2022)
In the community there is a need to more objectively evaluate the response of common chronic psychiatric disorders to treatment. Brain single photon emission computed tomography (SPECT) indirectly measures cerebral functional activity by uptake of a radiotracer, which follows regional cerebral blood flow. Brain 3D Thresholded SPECT scans are thresholded three dimensional images derived from brain SPECT data. A retrospective community study of longitudinal (before and after treatment) brain 3D Thresholded SPECT scans of 73 patients with all-cause psychiatric disorders (most frequent diagnostic clusters: attention-deficit hyperactivity disorder, post-mild traumatic brain injury, affective disorders, psychotic disorders, post-viral chronic syndromes), shows these baseline SPECT scans predict improvement (non-worsening to large improvement) in clinical functioning with a sensitivity of 94% (95% confidence interval 86-98%) and a specificity of 67% (95% confidence interval 21−94%). In contrast, contemporaneous analysis by the same radiologist of conventional 2D reading of the same before and after treatment brain SPECT scan data of the same 73 patients, predicted improvement (non-worsening to large improvement) in clinical functioning with a sensitivity of only 26% (95% confidence interval 17−37%) although with a specificity of 100% (95% confidence interval 44−100%). These data suggest 3D Thresholded SPECT scans can provide the clinician with a more objective measure for verifying improvement in psychiatric disorders seen in the community, consistent with prior studies of SPECT as a measure of neurobiological change. Furthermore, these data suggest 3D Thresholded SPECT scans may have clinical application in guiding treatment and potentially improving outcomes.